Dynamic Shear Properties of Recycled Waste Steel Slag Used as a Geo-Backfill Material. (2nd June 2019) - Wang, Liyan; Yan, Jiatao; Wang, Qi; Wang, Binghui; Gong, Wenxue
Abstract : Waste steel slag is a recycled industrial solid waste and is sometimes used as backfills, but the dynamic shear properties of waste steel slag have not been researched at present. To understand the dynamic shear properties of waste steel slag, the resonance column tests were carried out to investigate the dynamic shear modulus and damping ratio of the steel slag considering the effect of the relative density of steel slag and confining pressure. The maximum dynamic shear modulus was discussed, and the dynamic model of the steel slag was constructed by the Hardin–Drnevich model. The regression analysis of the normalized dynamic shear modulus ratio and damping ratio of the steel slag showed that the dynamic model was very fit for the steel slag. The comparisons of the dynamic shear properties of the steel slag with those of Nanjing fine sand and Fujian standard sand showed that the steel slag had similar dynamic shear resistance to Fujian standard sand and had potential to become a substitute for sand in the practical geotechnical engineering in the future.